Winter arsenic pollution in 10 forest ecosystems in the mountainous border regions of the Czech Republic - Petrash, Daniel A; Novák, Martin; Bohdálková, Leona; Krachler, Micheal; Čuřík, Jan; Veselovský, František; Štěpánová, Markéta; Umbría-Salinas, Karelys; Přechová, Eva; Komárek, Arnost (Environmental science and pollution research international, 2021)
Arsenic (As) concentrations and deposition fluxes were measured in snow and rime at 10 mountain-top sites near the borders between the Czech Republic and Austria, Germany, Poland, and Slovakia during three consecutive winter seasons (2009-2011). Our study was performed at a time following several decades of sharply decreasing regional atmospheric pollution and following the 2006 implementation of stricter air quality standards across Europe. Our objective was to compare vertical and horizontal depositions of soluble and insoluble As forms throughout the Czech Republic and define a recent Central European As pollution gradient. Arsenic soluble in weak nitric acid contributed 83 to 85% to the total As deposition, with the remaining 17-15% bound to stable particulate forms. The highest As deposition rates were recorded in the eastern Czech Republic near the borders with Poland and Slovakia. Complementary hydrochemical monitoring in four mountain-slope catchments situated near selected main study sites revealed a further decrease in open-area As deposition by the end of 2018 in the east of the country. In contrast, spruce canopy throughfall flux did not change significantly between 2009-2011 and 2016-2018. The site-specific relative roles of coal-burning-derived and ore-smelting-derived atmospheric As are discussed.
Keywords: Forests; Germany; Seasons; Europe; monitorování životního prostředí; lesy; Slovakia; arsen; Evropa; Austria; Německo; roční období; Air Pollutants; Czech Republic; Environmental Monitoring; Arsenic; ekosystém; Česká republika; Ecosystem; Slovenská republika; Poland; látky znečišťující vzduch; Rakousko; Polsko